Advances in computing and network communications proceedings of CoCoNet 2020 - Thampi, Sabu M.; Gelenbe, Erol; Atiquzzaman, Mohammed; Chaudhary, Vipin; Li, Kuan-Ching (Lecture Notes in Electrical Engineering, 2021)
This book constitutes the thoroughly refereed post-conference proceedings of the 4th International Conference on Computing and Network Communications (CoCoNet'20), October 14–17, 2020, Chennai, India. The papers presented were carefully reviewed and selected from several initial submissions. The papers are organized in topical sections on Signal, Image and Speech Processing, Wireless and Mobile Communication, Internet of Things, Cloud and Edge Computing, Distributed Systems, Machine Intelligence, Data Analytics, Cybersecurity, Artificial Intelligence and Cognitive Computing and Circuits and Systems. The book is directed to the researchers and scientists engaged in various fields of computing and network communication domains.